1986
DOI: 10.1136/pgmj.62.731.871
|View full text |Cite
|
Sign up to set email alerts
|

Primary carcinoma of the gall bladder associated with ulcerative colitis

Abstract: Summary:The report concerns a case of primary carcinoma of the gall bladder in a 53 year old man, who, 13 years previously underwent a pan-proctocolectomy for ulcerative colitis. Previous reports are reviewed, highlighting the difficulty of early diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Of 27 cases reported previously, most were found incidentally by autopsy, during cholecystectomy concomitantly performed with colectomy due to UC, or at a late stage requiring liver transplantation. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although previous authors have warned that gallbladder lesions also develop with a high incidence in PSC patients, such recognition seems not to be remembered sufficiently. 17 This is probably the first report of early GBC in a PSC and UC patient that was found before the operation and curatively resected.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of 27 cases reported previously, most were found incidentally by autopsy, during cholecystectomy concomitantly performed with colectomy due to UC, or at a late stage requiring liver transplantation. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Although previous authors have warned that gallbladder lesions also develop with a high incidence in PSC patients, such recognition seems not to be remembered sufficiently. 17 This is probably the first report of early GBC in a PSC and UC patient that was found before the operation and curatively resected.…”
Section: Discussionmentioning
confidence: 98%
“…Our literature survey found only 27 GBCs in PSC patients. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] …”
Section: Introductionmentioning
confidence: 99%
“…Few studies reported the risk to develop gall‐bladder cancer in IBD . The largest one found two gall‐bladder carcinomas among 67 patients with IBD and dominant stenosis PSC, whereas no cases of cancer were observed among 53 patients with IBD and no dominant stenosis PSC .…”
Section: Cholelithiasismentioning
confidence: 99%
“…The largest one found two gall‐bladder carcinomas among 67 patients with IBD and dominant stenosis PSC, whereas no cases of cancer were observed among 53 patients with IBD and no dominant stenosis PSC . Of note, six studies reported cases of gall‐bladder carcinomas associated with IBD …”
Section: Cholelithiasismentioning
confidence: 99%
“…Several case reports have been published on the occurrence of gallbladder carcinoma in both ulcerative colitis [32][33][34][35][36] and PSC [37-44,45 ,46-49]. There are also notions of incidental [15,50,51] and clinical manifest [52] gallbladder carcinoma in larger series of PSC patients.…”
Section: Polypoid Lesions Of the Gallbladder And Gallbladder Carcinommentioning
confidence: 91%